Model entrepreneurship based on ecotheology education: pesantren strategies in realizing sustainable development goals (SDGs) in Indonesia - Musleh Wahid (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The growing urgency of achieving the Sustainable Development Goals (SDGs) has highlighted the need for innovative educational models that integrate ethical values with practical actions, particularly within faith-based institutions. Islamic boarding schools (pesantren) possess strong potential to contribute to sustainability through their integrative educational systems, yet the connection between religious values and sustainable economic practices remains insufficiently explored. This study aims to analyze the integration of ecotheology education into entrepreneurship practices, examine the process of value internalization, and evaluate its implications for SDG-oriented character development among students. A qualitative approach with an intrinsic case study design was employed at an Islamic boarding school in Indonesia. Data were collected through in-depth interviews, participant observation, and document analysis involving 15 key informants, and analyzed using thematic analysis supported by NVivo software. The findings reveal that the integration occurs through a three-dimensional approach—curricular, cultural, and operational—enabling the transformation of ecotheological values into sustainable entrepreneurial practices. The internalization process follows a cyclical pattern involving value formation, habituation, implementation, and reflection, resulting in the emergence of a Santri Ecopreneur profile characterized by ecological awareness, economic competence, and social responsibility. This study concludes that ecotheology-based entrepreneurship provides a viable and replicable model for linking religious education with sustainable development practices, contributing both theoretically to integrative Islamic education and practically to the advancement of SDGs at the community level.